Islamic/State: Daesh's Visual Negotiation of Institutional Positioning. Issue 2 (3rd April 2021) - El Karhili, Nagham; Hendry, John; Kackowski, Wojciech; El Damanhoury, Kareem; Dicker, Aaron; Winkler, Carol
ABSTRACT: In response to calls for more empirical studies in organizational communication to further develop the Four Flows Model of CCO, this analysis examines Daesh's use of visual messaging strategies as a means of institutional positioning in the global communications environment. To do so, the study analyzes over 2000 religious and state images displayed in the group's English/Arabic publications. The findings highlight the critical role of both the quantity and nature of visual output in the Four Flows Model. The study also expands current understandings of institutional positioning over time, through organizational expansion/constraint, and in relation to various targeted online communities.